WAYS OF ENHANCEMENT OF FINANCIAL MANAGEMENT IN PUBLIC SECTOR - Victoria I. Pyatanova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
Public services are accompanied by a high level of expectations from the public, and therefore, we observe the strengthening role of supervision and quality management in this sector. The need for accountability and transparency in public expenses has grown significantly, which impacts public organizations and stimulates them to do more with less, be more effecient. The article considers practical aspects of enhancement of financial management, governance, performance management in organizations of this sector. The author emphasizes the qualification skills of financiers  in public sector under current conditions.